2014
DOI: 10.1371/journal.pone.0094812
|View full text |Cite
|
Sign up to set email alerts
|

Linked Production of Pyroglutamate-Modified Proteins via Self-Cleavage of Fusion Tags with TEV Protease and Autonomous N-Terminal Cyclization with Glutaminyl Cyclase In Vivo

Abstract: Overproduction of N-terminal pyroglutamate (pGlu)-modified proteins utilizing Escherichia coli or eukaryotic cells is a challenging work owing to the fact that the recombinant proteins need to be recovered by proteolytic removal of fusion tags to expose the N-terminal glutaminyl or glutamyl residue, which is then converted into pGlu catalyzed by the enzyme glutaminyl cyclase. Herein we describe a new method for production of N-terminal pGlu-containing proteins in vivo via intracellular self-cleavage of fusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 54 publications
0
25
0
1
Order By: Relevance
“…Cyclization is essential for the function of many peptides such as the hormones gastrin and thyrotropin-releasing hormone (TRH), the neuropeptide neurotensin, and proteins such as chemokines. 30,32 Of note, in several neurodegenerative disorders N-terminal pyroglutamate formation in neuronal peptides results in a higher tendency of aggregation and plaque formation due to the increased hydrophobicity and proteolytic stability, as shown for beta-amyloid (Aβ) deposition in Alzheimer's disease. 33 Protein N-termini can also be subject to lipid post-translational modification, where fatty acid chains (most frequently myristate or palmitate) are attached to free N-terminal glycines or to the side chain of an N-terminal cysteine.…”
Section: N-terminal Modificationsmentioning
confidence: 99%
“…Cyclization is essential for the function of many peptides such as the hormones gastrin and thyrotropin-releasing hormone (TRH), the neuropeptide neurotensin, and proteins such as chemokines. 30,32 Of note, in several neurodegenerative disorders N-terminal pyroglutamate formation in neuronal peptides results in a higher tendency of aggregation and plaque formation due to the increased hydrophobicity and proteolytic stability, as shown for beta-amyloid (Aβ) deposition in Alzheimer's disease. 33 Protein N-termini can also be subject to lipid post-translational modification, where fatty acid chains (most frequently myristate or palmitate) are attached to free N-terminal glycines or to the side chain of an N-terminal cysteine.…”
Section: N-terminal Modificationsmentioning
confidence: 99%
“…Recent studies have indicated that pGlu-modified protein production is a difficult process, where complex expression systems or postexpression treatment with purified QC is required (43, 44). As shown in this study, simple procedures can be used to tag, express, and purify secreted proteins from the WT and from Δ qc - 1 Δ qc - 2 strains.…”
Section: Discussionmentioning
confidence: 99%
“…Because pyroglutamate is ac ommon natural posttranslational modification, engineered access to pyroglutamatecontaining proteins is facile.Aprotein engineered to contain N-terminal Glp-His tag could be readily overexpressed in aproducing strain through av ariation of arecently reported expression system (Figure 4a). [22] In this expression system, co-expression of necessary protease and cyclase enzymes results in proteolytic cleavage to reveal an N-terminal glutamine residue,f ollowed by cyclization to produce pyroglutamate-containing protein. Consistent with that report, our strain produced Glp-His-tagged green fluorescence protein (GFP), with or without aglutathione S-transferase (GST) tag for affinity purification (Supporting Information for details).…”
Section: Zuschriftenmentioning
confidence: 99%